Internal Factors Risk of Breastfeeding Failure in Infants Age 3-6 Months - Kadir, Arisna; Yun Diniaty Rosidi, Indah (Program Studi Kebidanan Fakultas Kedokteran Universitas Sebelas Maret, 2022)
Background: The coverage of breastfeeding in Indonesia has not yet met the target set by the government . Mother's awareness of breastfeeding in Indonesia is only 14%, and is only given until the baby is four months old. Based on these data, there are ± 86% of mothers who experience exclusive breastfeeding failure, or we can say there are 86% of mothers who give additional food/drinks other than breast milk to their babies before the age of 6 months Objective: To determine the internal factors that cause the risk of breastfeeding failure in infants 3-6 months old. Method: analytic study with case control approach . Sampling using purposive sampling technique with a sample size of 10 respondents in the case group and 10 respondents in the control group. Statistical test using fisher exact test and odds ratio. Results: Internal factors that become the risk of breastfeeding failure in infants 3-6 months are occupation (OR = 16.00), parity (OR = 2.25) and mother's knowledge (OR = 21.00). While the internal factors of age, education, nutritional status and condition of the mother have a low risk for the failure of breastfeeding for infants 3-6 months. Conclusion: Efforts to increase knowledge are needed such as education and counseling. It is hoped that there will be a lactation counselor in increasing the coverage of breastfeeding.